Regulation of the regulators: Transcription factors controlling biosynthesis of plant secondary metabolites during biotic stresses and their regulation by miRNAs - Kajla, Mohini; Roy, Amit; Singh, Indrakant K.; Singh, Archana (Frontiers in Plant Science, 2023)
Biotic stresses threaten to destabilize global food security and cause major losses to crop yield worldwide. In response to pest and pathogen attacks, plants trigger many adaptive cellular, morphological, physiological, and metabolic changes. One of the crucial stress-induced adaptive responses is the synthesis and accumulation of plant secondary metabolites (PSMs). PSMs mitigate the adverse effects of stress by maintaining the normal physiological and metabolic functioning of the plants, thereby providing stress tolerance. This differential production of plant secondary metabolites is tightly orchestrated by master regulatory elements, Transcription factors (TFs) that express differentially or undergo transcriptional and translational modifications during stress conditions and influence the production of PSMs. Amongst others, microRNAs, a class of small, non-coding RNA molecules that regulate gene expression post-transcriptionally, also play a vital role in controlling the expression of many such TFs. The present review summarizes the role of stress-inducible TFs in synthesising and accumulating secondary metabolites and also highlights how miRNAs fine-tune the differential expression of various stress-responsive transcription factors during biotic stress.